The Effect of Smart Device Usage Among the Undergraduate’s Towards Academic Performance - Mohamed Elias, Ezanee; Lee, Jian Yuan; Mahidin, Norlila; Abu, Noor Hidayah; Hashim, Azizi; Abdullah, Ibrahim (UUM Press, 2021)
Almost all students at higher education institutions are now inseparably linked to their smart devices and have become increasingly reliant on them. So, the question of whether these devices can assist them to improve their academic performance or at least gain various benefits that improve the quality of learning through it arises. Therefore, the purpose of this study was to examine if there a relationship between smart device usage and academic performance among undergraduates’ in Universiti Utara Malaysia. The study employed quantitative method with a cross sectional time horizon and online survey with Google forms. A total of 473 students involved in the study, and the data was analysed using statistical software. The findings reveal there was a relationship between students' use of smart gadgets and their academic performance. Among the examples of such relationships are, addiction to using smart devices causes academic performance can decline. While the sharing of information and communication among students through the utilization of smart devices on the other hand can improve academic performance. Consequently, there are still negative matters related to these smart devices if they are obsessed with it without advisable self-control. So, there may be programs that can be organized by the university to manage this so as not to harm students’ health, social relationships, and weakening their academic achievement.